Epicardial Catheter Ablation of Ventricular Tachycardia in No Entry Left Ventricle. (April 2015) - Soejima, Kyoko; Nogami, Akihiko; Sekiguchi, Yukio; Harada, Tomoo; Satomi, Kazuhiro; Hirose, Takeshi; Ueda, Akiko; Miwa, Yousuke; Sato, Toshiaki; Nishio, Satoru; Shirai, Yasuhiro; Kowase, Shinya; et al.
<x xml:space="preserve">Abstract</x> Background— In patients with mechanical aortic and mitral valves and left ventricular tachycardia, catheter ablation may be prevented by limited access to the left ventricle. Methods and Results— In our series of 6 patients, 2 patients underwent direct surgical ablation and 4 underwent epicardial catheter ablation via a pericardial window. All patients had abnormal low voltage areas with fractionated or delayed isolated potentials on the apical epicardium. Most of the ventricular tachycardias were targeted by pace mapping. Sites with a good pace match or abnormal electrograms were ablated using an irrigated radiofrequency ablation catheter. A microscopic pathological evaluation of the resected tissue from 2 of the open-heart ablation patients revealed dense fibrosis on the epicardium compared with the endocardium, supporting the feasibility of an epicardial ablation for the ventricular tachycardia. Conclusions— Epicardial catheter ablation of ventricular tachycardia is a potentially useful therapy in patients who have mechanical aortic and mitral valves.